2014
DOI: 10.1007/s10113-014-0662-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing climate change readiness in Seychelles: implications for ecosystem-based adaptation mainstreaming and marine spatial planning

Abstract: The high financial costs and institutional constraints of adapting to climate change necessitate joint planning with other development and environmental priorities, especially in Small Island Developing States. In response, ecosystem-based adaptation (EbA) is gaining recognition as a cost-effective and synergistic approach for enhancing livelihoods through nature's services, building community resilience, and integrating marine spatial planning. Using Seychelles in the West Indian Ocean as a case study, we ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 41 publications
(48 reference statements)
0
41
0
2
Order By: Relevance
“…AR5 concluded that more work is needed on climate change and socio‐economic scenario modeling at the scale of small islands, the nature of adaptation barriers and limits, the links between adaptation and sustainable development, disaster risk reduction, and maladaptation, and comparative analyses of islands‐related research. This study finds that Khan and Amelie (2015), Kuruppu and Willie (2015), Mycoo (2017), Rhiney et al (2018), and Robinson (2017b) were among those publications that explicitly addressed these gaps, suggesting that the Small Islands Chapter played a role in shaping the research agenda on climate change adaptation in SIDS.…”
Section: Discussionmentioning
confidence: 87%
“…AR5 concluded that more work is needed on climate change and socio‐economic scenario modeling at the scale of small islands, the nature of adaptation barriers and limits, the links between adaptation and sustainable development, disaster risk reduction, and maladaptation, and comparative analyses of islands‐related research. This study finds that Khan and Amelie (2015), Kuruppu and Willie (2015), Mycoo (2017), Rhiney et al (2018), and Robinson (2017b) were among those publications that explicitly addressed these gaps, suggesting that the Small Islands Chapter played a role in shaping the research agenda on climate change adaptation in SIDS.…”
Section: Discussionmentioning
confidence: 87%
“…Once the PCA axes were determined, potential progressive readiness indicators were then formulated with guidance from existing literature [4,[21][22][23][36][37][38][39][40][41]. Countries were then scored against these axes (dimensions) using the same binary technique as in Phase 1 in an attempt to capture their readiness progress across the PCA-generated readiness dimensions.…”
Section: Phase 2-determining the Readiness Dimensions And Indicatorsmentioning
confidence: 99%
“…In this case, integrated resilient development outcomes will entail societal well-being, gender-sensitive livelihoods, and sustainable production and consumption (Kilroy 2015 ). Similarly, ecosystem-based adaptation (EbA) outcomes will be influenced by restoration as well as land use planning that mitigates flooding impacts (Khan and Amelie 2015 ).…”
Section: Methodsmentioning
confidence: 99%